Therapeutic Peptides Methods and Protocols - Nixon, Andrew E.; Nixon, Andrew E. (Methods in Molecular Biology,, 2014)
Therapeutic Peptides: Methods and Protocols features biological methods for the preparation of peptide phage display libraries using both filamentous and lytic phage.  With contributions from renowned authors in the field, the book also explores selection and screening of the prepared peptide libraries for peptides with the desired function and the subsequent characterization of the identified peptides.  Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls.   Practical and dependable,  Therapeutic Peptides: Methods and Protocols is an ideal guide for researchers from all backgrounds seeking methods for the identification of therapeutic peptide candidates.